Metformin Increases Sarcolemma Integrity and Ameliorates Neuromuscular Deficits in a Murine Model of Duchenne Muscular Dystrophy - Dong, Xia; Hui, Tiankun; Chen, Jie; Yu, Zheng; Ren, Dongyan; Zou, Suqi; Wang, Shunqi; Fei, Erkang; Jiao, Huifeng; Lai, Xinsheng (Frontiers in Physiology, 2021)
Duchenne muscular dystrophy (DMD) is a genetic neuromuscular disease characterized by progressive muscle weakness and wasting. Stimulation of AMP-activated protein kinase (AMPK) has been demonstrated to increase muscle function and protect muscle against damage in dystrophic mice. Metformin is a widely used anti-hyperglycemic drug and has been shown to be an indirect activator of AMPK. Based on these findings, we sought to determine the effects of metformin on neuromuscular deficits in mdx murine model of DMD. In this study, we found metformin treatment increased muscle strength accompanied by elevated twitch and tetanic force of tibialis anterior (TA) muscle in mdx mice. Immunofluorescence and electron microscopy analysis of metformin-treated mdx muscles revealed an improvement in muscle fiber membrane integrity. Electrophysiological studies showed the amplitude of miniature endplate potentials (mEPP) was increased in treated mice, indicating metformin also improved neuromuscular transmission of the mdx mice. Analysis of mRNA and protein levels from muscles of treated mice showed an upregulation of AMPK phosphorylation and dystrophin-glycoprotein complex protein expression. In conclusion, metformin can indeed improve muscle function and diminish neuromuscular deficits in mdx mice, suggesting its potential use as a therapeutic drug in DMD patients